The UK forensic science regulator: Fit for purpose?. Issue 6 (25th February 2021) - Nsiah Amoako, Emmanuel; McCartney, Carole
Abstract: The role of Forensic Science Regulator (FSR), created in 2007, was established to assure the achievement and maintenance of forensic science service (FSS) provision that commands public confidence. The FSR works at an organizational level, to assure, and improve the quality of forensic service provision and manage the risks of quality failures by Forensic Service Providers (FSPs). Despite this apparent introduction of "regulation, " forensic science provision in the United Kingdom has continued to receive a critical assessment. FSPs are meant to voluntarily adopt the Regulator's quality standards, achieve and maintain accreditation, and comply with regulatory requirements and guidance, including reporting complaints and quality failures to the Regulator. The effectiveness of the FSR thus cannot be gauged by examination of the actions of the Regulator alone, but also requires evidence of impact upon FSPs. Using public data, supplemented by interviews with FSS providers, to facilitate an initial assessment of whether the FSR's role is "fit for purpose, " we outline five demands made of FSPs in delivering FSSs to the criminal justice system and the five objectives of the FSR to support and enhance the ability of FSPs to meet these demands. We provide a prefatory commentary on whether the FSR is able to effectively fulfill this purpose. It is argued that the FSR role in its current form cannot be considered "fit for purpose" when evidence of the impact of regulation is lacking. Finally, we briefly summarize "inhibitors" that prevent the FSR from being more effective. This article is categorized under: Jurisprudence and Regulatory Oversight > Expert Evidence and Narrative Abstract : Forensic scientists at work in laboratory.